Implementation of Credit Number Assessment for The Functional Position of Penata Kanselerai - Prameswari, Pritta D.; Arijanto , Agus (Politeknik Siber Cerdika Internasional, 2024)
The development of the performance assessment of the State Civil Apparatus (ASN) has improved over time with increasingly complex organizational adjustments and with new positions created with the aim of professionalism in the State Civil Apparatus profession. Credit Score Assessment in the Functional Position of Chancery Manager is a transition mechanism from the Job Implementation Assessment List (DP3) to a more complex performance assessment, namely Credit Score Assessment. The focus of this research is to reveal the mechanism for continuous performance assessment with the process of synchronizing the governance and distribution of Chancellor's Management with what is being done. The method used in this research uses qualitative methods. By using George Edward IV's policy theory which examines and reviews 4 (four) variables, namely, Communication, Resources, Attitude (Disposition or Attitude) and Organizational Structure (Bureaucratic Structure). The implementation of credit score assessment from these variables can be reviewed from upstream to downstream processes. In this research, the NVIVO series 14 application was used. The results of the interviews obtained were valid with several clusters on SOPs that had not been determined from the initial formation until the final assessment in 2022. The recommendation given was to create an Standart Operating Procedur (SOP) from the results of the evaluation of JFPK credit assessment numbers during the period. 2020 – 2022, and needs to be strengthened with a Management System that can produce effective and efficient document output.